2018
DOI: 10.29297/orbit.v2i1.77
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Implied Trust in Ethical Hacking

Abstract: This paper discusses the issues of implied trust in ethical hacking. Unlike many other long-established professions, such as lawyers, doctors, and accountants; ethical hackingis a relatively new profession.As a result, this profession does not currently have a uniformed or mandated code, nor does it require any form of licensing. Because ethical hackers could gain access to highly sensitive and confidential information and there is potential for misuse of such information, the need to ensure professionalism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…It is imperative to improve cybersecurity performance to combat the increasing sophistication and stealth approaches of malicious individuals compromising a system. The following study concurs with the Verizon data breach report that shows insiders caused 62% of breaches [44] The report also demonstrated that 60% and 53% of threats were from Asia and Australia, respectively. The Identity Theft Resource Centre (2017) identified 850 breaches that resulted in 16 million exposed records [45].…”
Section: Digital Crime Managementsupporting
confidence: 89%
“…It is imperative to improve cybersecurity performance to combat the increasing sophistication and stealth approaches of malicious individuals compromising a system. The following study concurs with the Verizon data breach report that shows insiders caused 62% of breaches [44] The report also demonstrated that 60% and 53% of threats were from Asia and Australia, respectively. The Identity Theft Resource Centre (2017) identified 850 breaches that resulted in 16 million exposed records [45].…”
Section: Digital Crime Managementsupporting
confidence: 89%
“…A critical question is whether it is ethical to spend time and money to teach students how to hack, and yet, they will work under pressure from the management. Cases of corporate espionage across social media and tech companies illustrate the extent of these issues (Georg et al , 2018, pp. 4–6).…”
Section: Ethical Considerations In Ethical Hacking Pedagogymentioning
confidence: 99%
“…Other students may end up pursuing private interests and freelance work outside the formal work structures. Furthermore, companies are also training their own professionals, implying that they may not need the services of graduate students (Georg et al , 2018, pp. 7–8).…”
Section: Ethical Considerations In Ethical Hacking Pedagogymentioning
confidence: 99%
“…Dolayısıyla gri şapkalılar da siyah şapkalılar gibi yasadışı kabul edilirler. Bu saldırganlar bireysel olabileceği gibi genelde ekip halinde çalışırlar, organizedirler ve para elde etmeyi amaçlarlar [14].…”
Section: Siber Saldırganlarunclassified